Interpersonal sensitivity and response to selective serotonin reuptake inhibitors in patients with acute major depressive disorder - Peters, Evyn M.; Yilmaz, Orhan; Li, Cindy; Balbuena, Lloyd (Journal of Affective Disorders, 2024)
Background: Patients with major depression often suffer from excessive interpersonal sensitivity, although it is not typically measured in antidepressant clinical trials. Preliminary evidence suggests selective serotonin reuptake inhibitors have the capacity to reduce interpersonal sensitivity. Methods: This was a pooled analysis of data from 1709 patients in three randomized, double-blind, placebo-controlled trials of fluoxetine and paroxetine for acute major depressive disorder. Depressive symptoms were assessed with the Hamilton Depression Rating Scale. A factor from the Symptom Checklist was used to assess interpersonal sensitivity. Our outcome of interest was change from baseline scores at the last assessment (up to 8 or 12 weeks, depending on the trial). Results: Both medications produced significantly greater reductions in interpersonal sensitivity relative to placebo. The effect of medication remained significant after controlling for depression improvement, which explained 18.5% of the variation in interpersonal sensitivity improvement among those treated with active medication. The effect of medication on depressive symptoms, relative to placebo, was not influenced by baseline interpersonal sensitivity. Limitations: The outcome measured interpersonal sensitivity over the last week, and the results do not necessarily reflect changes in long-standing, trait-like patterns of interpersonal sensitivity. Only two medications were studied. Conclusions: Selective serotonin reuptake inhibitors are effective at treating interpersonal sensitivity in acutely depressed patients. This appears to be a unique drug effect that is not only the result of depression improvement. Future clinical trials might benefit from assessing interpersonal sensitivity more routinely. (PsycInfo Database Record (c) 2024 APA, all rights reserved)
Keywords: Antidepressant; Antidepressant Drugs; Antidepressive Agents; Clinical trial; Depression; Depressive Disorder, Major; Double-Blind Method; Drug Sensitivity; Drug Therapy; Fluoxetine; Humans; Major Depression; Meta-analysis; Mood disorder; Paroxetine; Psychopharmacology; Selective Serotonin Reuptake Inhibitors; Serotonin Reuptake Inhibitors; Symptoms; Treatment Outcome